Printed radio frequency identification tag and preparation method thereof

By performing grid design in the small-ring structure of printed RFID tags and using a small layer of graphene and silver microsheets to mix materials, the problems of high cost of label materials and large slurry usage are solved, and cost reduction and performance guarantee are achieved.

CN119623503APending Publication Date: 2025-03-14CANGNAN ANTE SECURITY TECH

Patent Information

Application Number
CN202510161936.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The material cost of existing printed RFID tags is too high, which limits its large-scale application, and it is difficult to effectively implement the method of reducing the amount of slurry.

Method used

By rastering the electrical ring structure, the dipole and chip are connected by using the grid structure to adjust the impedance matching, and the amount of conductive paste is reduced. Mixing a small layer of graphene with silver microsheets is used as a conductive material to reduce the amount of silver and improve the reliability and processing performance of the slurry.

Benefits of technology

On the basis of ensuring RFID performance, the material cost of the tag is reduced, and the reliability and printing processing performance of the slurry are improved, achieving the lowest cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119623503A_ABST
    Figure CN119623503A_ABST
Patent Text Reader

Abstract

The invention discloses a printed radio frequency identification tag and a preparation method thereof, and relates to the field of radio frequency identification tags. The tag comprises a substrate, an antenna and a chip, the antenna comprises a dipole and an electric small ring, the dipole is of a hollow structure, the electric small ring is of a grid structure, the width of grid lines is 0.3 mm-0. 5mm, and the distance between the grid lines is 1-2.5 times of the width of the grid lines. According to the invention, the electric small ring is rasterized, the dipole and the chip are connected through the grid structure, the impedance matching is adjusted, the use amount of the conductive slurry is effectively reduced, and the cost minimization is realized on the basis of ensuring the performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of radio frequency identification tags, and in particular to a printed radio frequency identification tag and a preparation method thereof. Background Art

[0002] In the process of widespread application of radio frequency identification (RFID) technology, high cost has become the primary factor hindering its large-scale popularization. Although the traditional mainstream aluminum foil etching type RFID tag has certain advantages in material cost, its production process involves complex links such as strong acid etching, label bonding and packaging bonding. This not only requires a large amount of additional equipment cost, energy cost, labor cost and auxiliary material cost, resulting in high comprehensive cost, but also causes serious pollution to the environment.

[0003] In recent years, the emerging printed RFID tag technology has attracted extensive research attention because it can be directly printed on various substrates, showing the significant advantages of extremely low process cost and no environmental pollution. However, this technology currently relies on silver paste as a conductive material, which makes the material cost of the tag too high, greatly limiting its large-scale application.

[0004] The only way to reduce the cost of RFID tags is to reduce both process costs and material costs. For printed RFID tags, reducing material costs is mainly achieved through two paths: one is to reduce the cost of raw materials, and the other is to reduce the amount of raw materials used. At present, most research focuses on reducing the cost of raw materials, such as using low-cost copper paste or carbon-based (including graphite, graphene, carbon nanotubes, etc.) paste for label printing. However, due to the inherent characteristics of these materials, they have a large gap with silver paste in terms of performance and stability, and it is difficult to completely replace silver paste in most application scenarios.

[0005] In contrast, there are relatively few studies on reducing costs by reducing the amount of raw materials used. Among them, a more common method is to reduce the amount of conductive paste used in the tag by designing the dipole antenna as a hollow structure. The tag antenna consists of a dipole part and a small electric loop part. When the dipole antenna is hollowed out, the printing of the small electric loop becomes the main part of the conductive paste consumption. However, since the small electric loop plays a key role in matching the impedance of the antenna and the chip, hollowing it out can easily lead to mismatch between the antenna and the chip, making it a huge challenge to further reduce the amount of paste used. Summary of the invention

[0006] In order to break through the current technical bottleneck that the cost of RFID tag slurry usage is difficult to further reduce, the present application provides a printed radio frequency identification label and a preparation method thereof.

[0007] In a first aspect, the present application provides a printed radio frequency identification tag, which includes a substrate, an antenna and a chip, wherein the antenna includes a dipole and an electric small loop, the dipole is a hollow structure, the electric small loop is a grid structure, the grid line width is 0.3mm to 0.5mm, and the distance between the grid lines is 1 to 2.5 times the grid line width.

[0008] For example, when the gate line width is 0.3 mm, the gate line spacing is 0.3-0.75 mm.

[0009] Exemplarily, when the gate line width is 0.35 mm, the gate line spacing is 0.35-0.875 mm.

[0010] Good impedance matching needs to be achieved between the tag's antenna and chip to ensure efficient signal transmission. The electric loop plays an important role in impedance adjustment in the antenna. If the dipole structure is hollowed out, the impedance values ​​of the antenna and the chip will be mismatched, and the signal received by the antenna cannot be effectively transmitted to the chip for processing. This application grids the electric loop (equivalent to adding grid lines in the hollow structure) and uses a grid structure to connect the dipole and the chip. While adjusting the impedance matching, it effectively reduces the amount of conductive paste used, thereby minimizing costs while ensuring performance.

[0011] It should be noted that the line width and spacing are in a multiple relationship, so when the line width becomes smaller, the gate line spacing will also become smaller at the same time, and the gate line density will increase, which can ensure impedance matching. The gate line width is 0.3mm~0.5mm. If the line width is too wide, the amount of slurry will increase. If the line width is too narrow, some lines may be discontinuous, resulting in the circuit being unable to form a loop. The distance between the gate lines is 1~2.5 times the gate line width. If the gate line spacing is too small, the amount of slurry will increase. If the spacing is too large, the impedance mismatch between the antenna and the chip will occur.

[0012] In any of the above technical solutions, the line width of the dipole is 0.3 mm to 0.5 mm.

[0013] Exemplarily, the chip may be selected from any one of SMARTDUST RFID, Moza and NXP u9 chips.

[0014] Exemplarily, the substrate can be selected from any one of glossy paper, corrugated paper, PDMS, glass or PMMA.

[0015] In any of the above technical solutions, the conductive paste for antenna printing contains 20-40wt% silver microsheets and 5-10wt% few-layer graphene, and the work function difference between the silver microsheets and the few-layer graphene is less than 0.3eV. In any of the above technical solutions, the work function of the silver micro-sheet is 4.26 eV.

[0016] In any of the above technical solutions, the graphene is a few-layer graphene with 3 to 8 layers and a work function of 4.2 to 4.5 eV.

[0017] In any of the above technical solutions, the particle size of the silver micro-flakes is 1 to 15 microns.

[0018] In any of the above technical solutions, the method for preparing the few-layer graphene is as follows: The expandable graphite is subjected to microwave treatment for 20 to 30 seconds, and dihydro-levorotatory glucosone and triacetin are added in a ratio of 3 to 5:1, and ultrasonically exfoliated for 8 to 14 hours at a temperature below 55° C. to obtain a graphene solution; The graphene solution is centrifuged at 400-600 rpm, the supernatant is taken, passed through a 250-300 mesh sieve, and then centrifuged at 2000-3000 rpm, the precipitate is taken, and vacuum dried to obtain the result; And / or, the vacuum degree of the vacuum drying is less than 30 Pa, the temperature is 140-160° C., and the drying time is 6-10 hours.

[0019] The number of graphene layers peeled off under the above conditions is between 3 and 8 layers, and the work function of graphene in this range is between 4.2 and 4.5 eV, which has a good match with the silver microsheet and can reduce the contact resistance between silver and graphene.

[0020] In any of the above technical solutions, the average particle size of the expandable graphite is 400-600 meshes.

[0021] In any of the above technical solutions, the conductive paste for antenna printing comprises, by weight: 20-40% silver microflakes, 5-10% few-layer graphene, 40-60% organic carrier, and 8-15% resin.

[0022] The organic carrier is a mixture of one or more organic solvents, which is used to prepare the silver microsheets and / or few-layer graphene into a slurry and effectively dilute the resin to ensure the flowability and printing processing performance of the slurry.

[0023] In any of the above technical solutions, the preparation method of the conductive paste for antenna printing is: Stirring to form an organic carrier; mixing the organic carrier and the few-layer graphene in a weight ratio of 4 to 6:1, and stirring to obtain a graphene slurry; The graphene slurry, silver micro-sheets and resin are mixed, stirred and ground to obtain a conductive slurry.

[0024] In any of the above technical solutions, the resin includes one or more of polyurethane, acrylic resin, and epoxy resin.

[0025] This application uses a few-layer graphene / silver mixed slurry as the conductive slurry, which has the following advantages: First, under the premise of ensuring the performance of the antenna, the amount of silver used is reduced and the material cost is reduced. Secondly, graphene has excellent electrical properties, such as high carrier mobility, etc. After mixing with silver paste, it can form a synergistic conductive effect with silver microsheets. In the antenna, this synergistic effect can make the current transmission smoother, help improve the overall electrical performance of the antenna, and meet the requirements of different application scenarios for antenna sensitivity and transmission distance. Secondly, graphene has high chemical stability and can better resist external influences such as oxidation and corrosion, extend the service life of the antenna, and improve the reliability of the tag in different environments. Finally, graphene can improve the fluidity of the slurry, improve processing performance, reduce poor printing problems such as grid shortage and missed printing, and improve the accuracy of the antenna structure and the consistency of performance.

[0026] It is worth noting that in the few-layer graphene / silver mixed slurry, the work functions of graphene and silver materials must be matched to reduce the contact resistance between the two, thereby making the antenna more conductive, more efficient in signal transmission, reducing losses during signal transmission, and ensuring the stability and accuracy of the antenna when receiving and transmitting signals.

[0027] In a second aspect, the present application provides a method for preparing a printed radio frequency identification tag, comprising the following steps: The antenna is printed with conductive paste, wherein the dipole in the antenna structure is a hollow structure, the antenna line width is 0.3mm-0.5mm, the electric small loop is a grid structure, the grid line width is 0.3mm-0.5mm; the distance between the grid lines is 1-2.5 times the grid line width; After the printed antenna is dried, it is compacted by a roller; the chip is coupled to the antenna through a flip-chip bonding method, and after the chip and the antenna are connected by conductive glue, hot pressing is performed to complete the label processing; In any of the above technical solutions, the drying temperature is 110-130°C and the drying time is 20-60 minutes; In any of the above technical solutions, the pressure applied by the pressing roller is 5-8 MPa and the temperature is 150-170°C; In any of the above technical solutions, the hot pressing temperature is 130-150° C. and the time is 10-40 seconds.

[0028] In summary, this application has the following beneficial effects: The RFID antenna structure of the present application, based on the hollowing of the dipole, connects the chip through the small electric ring of the grid structure, effectively matches the impedance of the antenna and the chip, and reduces the amount of conductive paste used for printing, thereby further reducing the cost while ensuring the RFID performance. In addition, the present application uses few-layer graphene and silver as conductive materials, which further reduces the cost of the conductive paste while improving the reliability and printing processing performance of the paste. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 These are two structural diagrams of radio frequency identification tags in the embodiments of the present application.

[0030] Figure 2 1 is a structural diagram of the radio frequency identification tag in each embodiment and comparative example.

[0031] Figure 3 Spectral response diagrams of Example 1 and Comparative Example 3.

[0032] Figure 4 Enlarged diagram of lines of Example 1 and Comparative Example 5.

[0033] Description of reference numerals: 1. Chip; 2. Dipole; 3. Electric ring. DETAILED DESCRIPTION

[0034] Example 1, a printed radio frequency identification tag, is prepared as follows: Step 1: Microwave the 500-mesh expandable graphite in a household microwave oven for 30 seconds to weaken its interlayer force. After treatment, add it into a mixture of dihydro-levulin and triacetin in a mass ratio of 4:1, and ultrasonically peel it for 10 hours. During the peeling process, keep ice bath to ensure that the temperature is below 55°C.

[0035] Step 2: The exfoliated graphene solution was centrifuged at 500 rpm, and the supernatant was taken to remove the large particles that were not exfoliated in the precipitate; after passing through a 300-mesh steel sieve, the solution was centrifuged at 2500 rpm, and the precipitate was taken to remove the smaller graphene nanosheets in the supernatant. After drying in a vacuum oven (<30 Pa, 150°C, 8 hours), a few-layer graphene powder was obtained.

[0036] Step 3: Mix polyvinyl pyrrolidone and dihydro-levorotatory glucosone at a weight ratio of 1:100, stir at 300 rpm for 30 minutes to prepare a graphene organic carrier. Mix the graphene organic carrier and the few-layer graphene powder at a weight ratio of 5:1, stir at 350 rpm for 1 hour to obtain a graphene slurry.

[0037] Step 4: Mix the graphene slurry and the conductive silver paste (containing 60wt% silver microsheets, 20wt% silver paste organic carrier, and 20wt% polyurethane) in a weight ratio of 1:1, stir at 300rpm for 1 hour, and pass through a three-roll mill (32rpm, 89rpm and 250rpm) to form a conductive slurry. By weight percentage, the slurry contains 30% silver microsheets, 8% few-layer graphene (3 to 8 layers), 52% mixed organic carrier, and 10% polyurethane resin.

[0038] Step 5: Take a 260 mesh screen printing plate and press Figure 1(a) Structure The antenna is printed with the above conductive paste. In the antenna structure, dipole 2 is a hollow structure with a line width of 0.35 mm, and the electric ring 3 is a grid structure with a grid line width of 0.4 mm and a grid line spacing of 2 times the line width. After printing, the antenna is dried at 120°C for 30 minutes and passed through a 6MPa, 165°C roller press. Chip 1 (SMARTDUSTRFID) is coupled to the antenna by flip chip bonding. After connecting chip 1 and the antenna by conductive glue (DELOMONOPOX AC268), the RFID tag is processed by hot pressing at 140°C for 15s.

[0039] Embodiment 2, a printed RFID tag, is different from Embodiment 1 in that it uses Figure 1 (a) Antenna structure: in step 5, the grid line width is 0.35 mm, and the grid line spacing is 1 times the line width.

[0040] Embodiment 3, a printed RFID tag, is different from Embodiment 1 in that it uses Figure 1 (b) Antenna structure: in step 5, the grid line width is 0.35 mm, and the grid line spacing is twice the line width.

[0041] Embodiment 4, a printed RFID tag, is different from Embodiment 1 in that it uses Figure 1 (b) Antenna structure: in step 5, the grid line width is 0.35 mm, and the grid line spacing is 1 times the line width.

[0042] Embodiment 5, a printed RFID tag, is different from Embodiment 3 in that the ratios in steps 3 and 4 are different, as follows: Step 3: Polyvinyl pyrrolidone and dihydro-levorotatory glucosone were mixed at a weight ratio of 1:100, and stirred at 300 rpm for 30 minutes to prepare a graphene organic carrier. The graphene organic carrier and the few-layer graphene powder were mixed at a weight ratio of 7:1, and stirred at 350 rpm for 1 hour to obtain a graphene slurry.

[0043] Step 4: Mix the graphene slurry and the conductive silver paste (containing 70wt% silver microsheets, 14wt% silver paste organic carrier, and 16wt% polyurethane) in a weight ratio of 1:1, stir at 300rpm for 1 hour, and pass through a three-roll mill (32rpm, 89rpm and 250rpm) to form a conductive slurry. By weight percentage, the slurry contains 35% silver microsheets, 6% few-layer graphene (3 to 8 layers), 51% mixed organic carrier, and 8% polyurethane resin.

[0044] Comparative Example Comparative Example 1 is a printed radio frequency identification tag, which differs from Example 1 in that a conductive silver paste (containing 60 wt % silver microflakes, 20 wt % silver paste organic carrier, and 20 wt % polyurethane) is used in step 5, and the dipole and the electric small ring in the antenna structure are both solid structures.

[0045] Comparative Example 2 is a printed radio frequency identification tag, which is different from Example 1 in that the dipole and the electric loop in the antenna structure in step 5 are both solid structures.

[0046] Comparative Example 3 is a printed radio frequency identification tag, which is different from Example 1 in that the dipole in the antenna structure in step 5 is a hollow structure, and the electric small loop is a solid structure.

[0047] Comparative Example 4 is a printed radio frequency identification tag, which is different from Example 1 in that the dipole in the antenna structure in step 5 is a hollow structure, and the electric small loop is a hollow structure (without grid lines).

[0048] Comparative Example 5 is a printed radio frequency identification tag, which is different from Example 1 in that the dipole in the antenna structure in step 5 is a hollow structure, the electric small loop is a solid structure, and the line width is 0.2 mm.

[0049] Comparative Example 6, a printed RFID tag, is different from Example 1 in that the dipole in the antenna structure in step 5 is a grid structure with a line width of 0.35 mm, a grid line width of 0.35 mm, and a grid line spacing of 0.5 times the line width.

[0050] Comparative Example 7, a printed RFID tag, is different from Example 1 in that in step 5, the antenna structure is as follows: Figure 1 (b) Conductive silver paste (containing 60wt% silver microflakes, 20wt% silver paste organic carrier, and 20wt% polyurethane) is used. The dipoles and electric rings in the antenna structure are both solid structures.

[0051] Comparative Example 8, a printed RFID tag, is different from Comparative Example 1 in that the antenna structure in step 5 is as follows: Figure 1 (b) The dipole and electric loop in the antenna structure are both solid structures.

[0052] Comparative Example 9, a printed RFID tag, is different from Comparative Example 1 in that the antenna structure in step 5 is as follows: Figure 1 (b) In the antenna structure, the dipole is a hollow structure with a line width of 0.35 mm, and the electric loop is a solid structure.

[0053] Comparative Example 10, a printed RFID tag, differs from Comparative Example 1 in that the dipole in the antenna structure in step 5 is a grid structure with a line width of 0.35 mm, a grid line width of 0.35 mm, and a grid line spacing of 0.5 times the line width.

[0054] Performance testing 1. Reading distance comparison: Test method: Voyantic's Tagformance Pro RFID (EIRP 30dBm, reverse accuracy -18dBm) system is used to test key parameters such as forward tag power and radar reflection area in the 860MHz-960MHz range, and the internal algorithm of Tagformance Pro converts them into theoretical forward and reverse reading distances. The minimum value between the two at each frequency point is taken as the tag reading distance at that frequency.

[0055] Table 1. Reading distance of each example

[0056] Referring to Table 1, the reading distances of Examples 1-3 and their comparative examples with similar structures are all higher than those of Examples 4 and 5 and their comparative examples with similar structures (except Comparative Examples 4 and 5). This is because the antenna structures of Examples 1 to 3 are longer (11 cm) and have higher structural radiation efficiency, but Example 4 has a smaller structural size and can be applied to more diverse scenarios.

[0057] The maximum reading distance of Examples 1 and 2 is slightly smaller than that of Comparative Example 1, and the maximum reading distance of Examples 3 and 4 is slightly smaller than that of Comparative Example 7. This is because replacing silver powder with graphene will reduce the conductivity of the silver paste and affect the radiation efficiency of the antenna. However, the reduction in the maximum reading distance is not obvious (<10%), indicating that in this application scenario, replacing silver powder with graphene can reduce costs while having little impact on performance.

[0058] Comparing Examples 1 and 2 with Comparative Examples 3 and 6, it is found that the reading distances are almost the same, indicating that the hollowing of the antenna and the rasterization of the small electric ring can save slurry while hardly affecting the reading performance of the final tag. The performance of Comparative Examples 3 and 4 is also almost the same as that of Comparative Examples 9 and 10, indicating that the rasterization strategy can be applied to different types of antenna structures.

[0059] The reading distance of Comparative Example 4 is almost 0, which shows that although directly hollowing out the small electric ring can further reduce the amount of slurry, it will cause a serious offset in impedance matching and cause the label to fail. The reading distance of Comparative Example 5 is 0, and it can be observed under a microscope that some printed lines are discontinuous ( Figure 4 ), indicating that although reducing the line width can further reduce the label cost, when the line width is lower than the screen printing accuracy, the line may be discontinuous and cause the label to become inactive.

[0060] 2. Antenna material cost comparison The formula for estimating antenna material cost is: slurry cost × antenna slurry weight The cost of silver paste is the market purchase price, and the cost of silver / graphene mixed paste is silver paste price × 0.5 + graphene paste cost × 0.5.

[0061] The method for estimating the weight of antenna slurry is as follows: measure the weight of 10 sheets of glossy paper using a high-precision balance (m1), print the corresponding antenna on the glossy paper and weigh it again (m2), then the slurry consumption for a single antenna is (m2-m1) / 10.

[0062] Since the tag reading distance of Comparative Examples 4 and 5 is 0 and has no practical value, no cost calculation is performed.

[0063] Table 2. Cost estimates for each case

[0064] Referring to Table 2, compared with the mainstream printing processing methods of the two antennas (silver paste, solid dipole, solid electric ring), such as Comparative Examples 1 and 7, the material costs of Example 1 and Example 4 were reduced by 88% and 79% respectively when the performance attenuation was less than 10%. Compared with the existing optimal methods (graphene / silver conductive paste, hollow dipole, solid electric ring), such as Comparative Examples 3 and 9, this example reduces the cost by more than 30% (35% and 46%) by gridding the electric ring without any performance attenuation.

[0065] The market price of aluminum foil etched antennas is generally between 0.009 and 0.015 yuan, which is close to the price of this application. However, since the subsequent process of aluminum foil labels is much higher than that of printed labels (the combined depreciation of equipment, labor and energy costs for the secondary packaging or label laminating process are generally between 0.05 and 0.08 yuan), its comprehensive coding cost is much higher than that of this achievement.

[0066] 3. Antenna spectrum response Figure 3 The forward and reverse reading distance diagrams of Example 1 (gridding of the electric small ring, line width of 0.35mm, and grid spacing of 2 times the grid line width) and Comparative Example 6 (non-gridding of the electric small ring) are almost identical in response intensity and peak range, proving that the gridding of the electric small ring has no effect on the antenna / chip impedance matching under the conditions of this example.

[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A printed radio frequency identification tag, characterized in that: It comprises a substrate, an antenna and a chip. The antenna comprises a dipole and an electric small ring. The dipole is a hollow structure. The electric small ring is a grid structure. The grid line width is 0.3mm-0.5mm. The distance between grid lines is 1-2.5 times of the grid line width.

2. The label according to claim 1, characterized in that: The conductive paste for antenna printing contains 20-40 wt% of silver microsheets and 5-10 wt% of graphene, and the work function difference between the silver microsheets and the graphene is less than 0.3 eV.

3. The label according to claim 2, characterized in that: The graphene is a few-layer graphene with 3 to 8 layers and a work function of 4.2 to 4.5 eV.

4. The label according to claim 3, characterized in that: The method for preparing the few-layer graphene is as follows: The expandable graphite is subjected to microwave treatment for 20 to 30 seconds, and dihydro-levorotatory glucosone and triacetin are added in a ratio of 3 to 5:1, and ultrasonically exfoliated for 8 to 14 hours at a temperature below 55° C. to obtain a graphene solution; The graphene solution is centrifuged at 400-600 rpm, the supernatant is taken, passed through a 250-300 mesh sieve, and then centrifuged at 2000-3000 rpm, the precipitate is taken, and vacuum dried to obtain the result; And / or, the vacuum degree of the vacuum drying is less than 30 Pa, the temperature is 140-160° C., and the drying time is 6-10 hours.

5. The label according to claim 4, characterized in that: The average particle size of the expandable graphite is 400-600 meshes.

6. The label according to claim 1, characterized in that: The line width of the dipole is 0.3 mm to 0.5 mm.

7. The label according to claim 2, characterized in that: In parts by weight, the conductive paste for antenna printing comprises: 20-40% silver micro-sheets, 5-10% graphene, 40-60% organic carrier, and 8-15% resin.

8. The label according to claim 7, characterized in that: The preparation method of the conductive paste for antenna printing is: Polyvinyl pyrrolidone and dihydro-levorotatory glucosone are mixed in a weight ratio of 1:80 to 120, and stirred to prepare an organic carrier; the organic carrier and few-layer graphene are mixed in a weight ratio of 4 to 6:1, and stirred to obtain a graphene slurry; Mixing graphene slurry, silver microsheets and resin, stirring and grinding to obtain conductive slurry; And / or, the resin includes one or more of polyurethane, acrylic resin, and epoxy resin.

9. The label according to claim 1, characterized in that: The substrate includes glossy paper, corrugated paper, PDMS, glass or PMMA.

10. A method for preparing a printed radio frequency identification label, characterized in that: The steps include: The antenna is printed with conductive paste, wherein the dipole in the antenna structure is a hollow structure, the electric small loop is a grid structure, the grid line width is 0.3mm to 0.5mm, and the distance between the grid lines is 1 to 2.5 times the grid line width; After the printed antenna is dried, it is compacted by a roller; the chip is coupled to the antenna through a flip-chip bonding method, and after the chip and the antenna are connected by conductive glue, hot pressing is performed to complete the label processing; And / or, the drying temperature is 110-130° C. and the drying time is 20-60 min; And / or, the pressure applied by the pressing roller is 5-8 MPa and the temperature is 150-170°C; And / or, the temperature of the hot pressing is 130-150° C., and the time is 10-40 seconds.

Citation Information

Patent Citations

  • Coupled feeding horizontal omni-directional annular radio frequency identification (RFID) label antenna

    CN103151616A

  • Self-similar structure broadband radio frequency identification tag

    CN103646277A

  • Long-distance radio frequency identification (RFID) label

    CN106099338A

  • Hollow-type dipole antenna and fabric-based UHF RFID tag

    CN108565550A

  • Hollowed-out dipole antenna and printed RFID tag

    CN111898722A

Cited By

  • Radio frequency identification tag and manufacturing method thereof

    CN119990173A